Report of the Zamindari Abolition Committee - Planning Commission (Planning Commission, 1958)
Shri P. N. Kaul’s continuance as a Member of the Committee.— On relinquishing charge of the post of Revenue Secretary to Government on his appointment as Settlement Commissioner, Rajasthan, Shri P. N. Kaul continued—under instructions from the Revenue Minister—to work as a Member of the Committee.
Government of Rajasthan (Revenue Department)
Government of Rajasthan (Revenue Department)